Learning Smart in Home - Alexander Kiy; Dustin Wegner (FernUniversität Hagen, 2020)
Developments in the Smart Home sector are increasingly supporting users in their everyday lives and at home. The devices are intelligent, networked and integrated into the environment. With Intelligent Personal Assistants (IPAs), systems have recently made their way into the living room at home. However, the part of formal and informal learning with Intelligent Personal Assistants is not yet exhausted. Yet, IPAs offer an innovative approach to rethink for example classic learning methods with flashcards or partner learning. Are they feasible to support learning at home? IPAs can be used to provide knowledge and can be used for a variety of ways for assessment. This article presents an IPA using the wide-spread Amazon Echo as a realization of a virtual learning partner. Therefore, the prototype combines aspects from the domain of Intelligent Tutoring Systems and the domain of Learning Analytics with the help of a Learning Record Store (xAPI). The presented prototype was evaluated according to the Technology Acceptance Model. The articles closes with conceivable scenarios how IPAs will be able to adapt the physical environment according to the learning goal.